Effects of bovine serum on foal IgG levels - Dirks, Katherine; Homme, Brett; Sinclair, Chelsea; Kouba, Joann M. (My University, 2017)
Studies have shown increased immunoglobulin G (IgG) levels in newborn calves after receiving bovine serum, suggesting an improved level of passive transfer. There is limited data available regarding the effects in newborn foals. Therefore, the objective of this trial is to determine if providing a bovine serum supplement will result in increased IgG concentrations in the foal. If so, it could help improve the absorption of antibodies and lessen the likelihood of an illness in the foal by providing better protection against diseases. This trial is using 15 pregnant mares, 8 of which are being provided the supplement and 7 are receiving a placebo. The supplement used is LIFELINE Elite, commonly marketed and used to reduce inflammation in performance horses, and contains the active ingredient BioThrive, which is derived from bovine serum. Lifeline is being supplemented in the mare’s grain at 115 gr twice per day beginning 60 days prior to the mare’s expected foaling date and continuing until 10 days after parturition. Once the mare foals, a 10 mL blood sample is collected from the foal within an hour and prior to the foal suckling for the first time. Blood is also collected around 30 hours post-partum. The IgG concentration in the blood samples will be tested this summer using an IgG ELISA. Colostrum samples were also collected at parturition and evaluated immediately for IgG concentrations. Two products are being used to test the colostrum. The Colostrometer, which is a hydrometer testing for specific gravity of a solution compared to distilled water, and the Brix Refractometer which measures the refractive index of a solution. Although research is still ongoing, colostrum data from 10 mares has been collected and the data is provided below. So far, the data does not appear to suggest an improvement in colostrum quality following supplementation.
Keywords: Spring 2017